Antiviral Activity and Toxicity Prediction of Compounds Contained in Figs (Ficus carica L.) by In Silico Method - Sophi Damayanti; Khonsa Khonsa; Tasia Amelia (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Viral infection is a global health problem that can cause endemic to pandemic. Compounds delivered from plants has been developed as an alternative antiviral agent. One of the plants that can be used as antiviral therapy is Ficus carica L. (figs). The aim of this research is to predict the inhibitory activity and toxicity of compounds contained in figs as an antiviral for HIV-1 using in silico method. Compounds were docked to the HIV-1 Reverse Transcriptase protein (PDB ID: 3LAL). Threedimentional structures were modeled using GaussView and optimized using Gaussian 09W. Optimized compounds were docked to the target protein using AutoDock Tools and the interaction to protein binding side were analyzed in comparison with the standard compounds. The standard compound used for the analysis nevirapine, efavirenz, and doravirine. The compound toxicity was analyzed using ECOSAR and Toxtree. Based on the results, the compounds that has similar interaction to the standard compounds were campesterol which has 4 similar hydrophobic interactions. Based on the classification of Cramer Rules for toxicity test, campesterol are classified in class 3 (high toxicity) and according to the Benigni/Bossa Rulebase classification, campesterol are negative for genotoxic and nongenotoxic carcinogenicity.Keywords: Antivirus, HIV, figs, molecular docking, toxicity